Changes Implemented During a Workplace Psychosocial Intervention and Their Consistency With Intervention Priorities. Issue 3 (March 2015) - Gilbert-Ouimet, Mahée; Baril-Gingras, Geneviève; Cantin, Viviane; Leroux, Isabelle; Vézina, Michel; Trudel, Louis; Bourbonnais, Renée; Brisson, Chantal
Abstract : Objectives: To describe the changes implemented as part of a workplace psychosocial intervention. Methods: The intervention was conducted in a public organization employing 1630 white-collar workers. The intervention was defined as all changes implemented to reduce adverse psychosocial work factors. A logbook was held to describe the changes implemented in the intervention group and in a comparable control group ( N = 1282). Results: Social support and reward were the psychosocial factors most targeted (41% to 83%). In comparison with the control group, the intervention group implemented four times more major changes and implemented changes, improving the employees' workload. Conclusions: Changes mainly targeted social support and reward. The intervention group implemented four times more major changes than the control group. The intervention group implemented changes targeting the workload, whereas no such changes were implemented in the control group. Abstract : Supplemental Digital Content is Available in the Text.